Detection of pesticides on tomato fruit surface by ultraviolet matrix-assisted laser desorption/ionization mass spectrometry - Gholipour, Y. (2012)
Small amounts of pesticides and their transformation products may exist on edible parts before harvesting tomato (Solanum lycopersicum L.) fruits. For analyzing these compounds, special techniques with minimum preparations and high sensitivity are needed. The capability of a technique for in situ detection of target chemicals can be also a great advantage. Here we report the applicability of ultraviolet matrix-assisted laser desorption/ionization time of flight mass spectrometry (UV-MALDI TOF MS) for direct detection of pesticides and the residues on the tomato fruit surface. Fruits grown in the hydroponic system in a greenhouse were sprayed with a mixture of four pesticides including benomyl, triforine, milbemycin and malathion and collected one week later. The pericarp of sprayed and control fruits was peeled and located on a UV-MALDI plate, air-dried and covered with carbon nanotubes or 2,5-dihydroxybenzoic acid as matrixes. Signals of active and supplementary compounds which are normally present in commercial pesticides could be analyzed and directly detected on the surface of cuticle. A malathion degradation product was also detected on the sprayed fruit pericarp.